# Extensions 1→N→G→Q→1 with N=C22 and Q=C22×A4

Direct product G=N×Q with N=C22 and Q=C22×A4
dρLabelID
A4×C2448A4xC2^4192,1539

Semidirect products G=N:Q with N=C22 and Q=C22×A4
extensionφ:Q→Aut NdρLabelID
C22⋊(C22×A4) = C22×C22⋊A4φ: C22×A4/C24C3 ⊆ Aut C2212C2^2:(C2^2xA4)192,1540
C222(C22×A4) = C2×D4×A4φ: C22×A4/C2×A4C2 ⊆ Aut C2224C2^2:2(C2^2xA4)192,1497

Non-split extensions G=N.Q with N=C22 and Q=C22×A4
extensionφ:Q→Aut NdρLabelID
C22.1(C22×A4) = C22×C42⋊C3φ: C22×A4/C24C3 ⊆ Aut C2224C2^2.1(C2^2xA4)192,992
C22.2(C22×A4) = C2×C24⋊C6φ: C22×A4/C24C3 ⊆ Aut C22126+C2^2.2(C2^2xA4)192,1000
C22.3(C22×A4) = C2×C42⋊C6φ: C22×A4/C24C3 ⊆ Aut C22246C2^2.3(C2^2xA4)192,1001
C22.4(C22×A4) = C2×C23.A4φ: C22×A4/C24C3 ⊆ Aut C22126+C2^2.4(C2^2xA4)192,1002
C22.5(C22×A4) = C24.6A4φ: C22×A4/C24C3 ⊆ Aut C221612+C2^2.5(C2^2xA4)192,1008
C22.6(C22×A4) = C24⋊A4φ: C22×A4/C24C3 ⊆ Aut C221612+C2^2.6(C2^2xA4)192,1009
C22.7(C22×A4) = A4×C4○D4φ: C22×A4/C2×A4C2 ⊆ Aut C22246C2^2.7(C2^2xA4)192,1501
C22.8(C22×A4) = C2×D4.A4φ: C22×A4/C2×A4C2 ⊆ Aut C2232C2^2.8(C2^2xA4)192,1503
C22.9(C22×A4) = 2- 1+43C6φ: C22×A4/C2×A4C2 ⊆ Aut C22324C2^2.9(C2^2xA4)192,1504
C22.10(C22×A4) = A4×C42central extension (φ=1)48C2^2.10(C2^2xA4)192,993
C22.11(C22×A4) = A4×C22⋊C4central extension (φ=1)24C2^2.11(C2^2xA4)192,994
C22.12(C22×A4) = A4×C4⋊C4central extension (φ=1)48C2^2.12(C2^2xA4)192,995
C22.13(C22×A4) = C2×C4×SL2(𝔽3)central extension (φ=1)64C2^2.13(C2^2xA4)192,996
C22.14(C22×A4) = C4×C4.A4central extension (φ=1)64C2^2.14(C2^2xA4)192,997
C22.15(C22×A4) = (C2×Q8)⋊C12central extension (φ=1)32C2^2.15(C2^2xA4)192,998
C22.16(C22×A4) = C4○D4⋊C12central extension (φ=1)64C2^2.16(C2^2xA4)192,999
C22.17(C22×A4) = A4×C22×C4central extension (φ=1)48C2^2.17(C2^2xA4)192,1496
C22.18(C22×A4) = C23×SL2(𝔽3)central extension (φ=1)64C2^2.18(C2^2xA4)192,1498
C22.19(C22×A4) = C2×Q8×A4central extension (φ=1)48C2^2.19(C2^2xA4)192,1499
C22.20(C22×A4) = C22×C4.A4central extension (φ=1)64C2^2.20(C2^2xA4)192,1500
C22.21(C22×A4) = C2×Q8.A4central extension (φ=1)48C2^2.21(C2^2xA4)192,1502
C22.22(C22×A4) = SL2(𝔽3)⋊5D4central stem extension (φ=1)32C2^2.22(C2^2xA4)192,1003
C22.23(C22×A4) = D4×SL2(𝔽3)central stem extension (φ=1)32C2^2.23(C2^2xA4)192,1004
C22.24(C22×A4) = SL2(𝔽3)⋊6D4central stem extension (φ=1)64C2^2.24(C2^2xA4)192,1005
C22.25(C22×A4) = SL2(𝔽3)⋊3Q8central stem extension (φ=1)64C2^2.25(C2^2xA4)192,1006
C22.26(C22×A4) = Q8×SL2(𝔽3)central stem extension (φ=1)64C2^2.26(C2^2xA4)192,1007

׿
×
𝔽